(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Ferro cement is a thin, versatile construction material, with several unique properties and suitable for wide range of applications in Civil Engineering. Generally concrete structures are designed for static loads but sometimes dynamic loads like blasts etc. Prefabricated elements are used in construction industry as an alternative system to overcome the formwork problems in addition to getting better quality control. The prefabricated elements made of reinforced concrete are extremely heavy and difficult to transport, placing in position and to construct. Because of its good structural performance and low cost ferrocement is used in construction industry. Ferrocement is suitable for the construction of roofingfloor elements, precast units, manhole covers, and construction of domes, vaults, grid surface and folded plates. So finding the flexural behavior of ferrocement is necessary. Therefore, the flexural strength is determined by varying the meshes in the U-section and varying the thickness of the beam. An experimental and finite element analysis on flexural behavior of ferrocement U-shape channel section reinforced with wire mesh with varying number of wire mesh layers is presented. Finite element analysis of U-shape ferrocement channel was carried out. The finite element analysis (FEA) has been also used to model the ferrocement U-shape channel for various span and thickness. Ferrocement U-shape channel with varies thickness and number of mesh layers analyzed in ANSYS.